2012
DOI: 10.1136/archdischild-2011-300435
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomised clinical assay to evaluate the efficacy of probiotics in preterm newborns weighing less than 1500 g in the prevention of necrotising enterocolitis

Abstract: Probiotics may offer potential benefits for premature infants and are a promising strategy in the reduction of the risk of NEC in preterm newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 31 publications
2
98
0
1
Order By: Relevance
“…Breast milk feeding initiation rates were high (96.9%) in both groups, compared with other studies. 13,14,[22][23][24]33 Our findings emphasize the importance of performing well-powered trials of probiotic administration in very preterm infants in different settings.…”
Section: Discussionmentioning
confidence: 96%
“…Breast milk feeding initiation rates were high (96.9%) in both groups, compared with other studies. 13,14,[22][23][24]33 Our findings emphasize the importance of performing well-powered trials of probiotic administration in very preterm infants in different settings.…”
Section: Discussionmentioning
confidence: 96%
“…102 Numerous studies have evaluated the use of probiotics to supplement colonization of the preterm gut with commensal flora, and thereby reducing the incidence of NEC. [103][104][105][106][107] However, there has been wide variation in the timing, dose, and formulation of probiotics used in the various trials. A Cochrane systematic review evaluating the use of probiotics in the prevention of NEC showed a statistically significant reduction in the incidence of NEC and mortality in the probiotics group (NEC RR 0.35, 95% CI 0.24-0.52 and mortality RR 0.40, 95% CI 0.27-0.60).…”
Section: Current Research Focus Probioticsmentioning
confidence: 99%
“…The B. lactis used by Mihatsch et al 36 was checked monthly to ensure the viability and purity of the product together with the 24-hour stability of the prepared suspension. The six-strain product used by Fernández-Carrocera et al 40 (four strains of Lactobacillus, one of B. infantis and one of S. thermophilus) was checked twice against the manufacturer's quality control register and the ABC Dophilus used for the ProPrems trial 41 was imported under licence into Australia. Each batch was then subjected to independent confirmation of taxonomy and quality by checking the probiotic content using polymerase chain reaction (PCR) and the purity by culture.…”
Section: Qualitymentioning
confidence: 99%